Artificial intelligence : a modern approach - Russell, Stuart J. (Stuart Jonathan); Norvig, Peter (Pearson series in artificial intelligence, 2022)
"Updated edition of popular textbook on Artificial Intelligence. This edition specific looks at ways of keeping artificial intelligence under control"--